THE EFFECT OF TRAINING ON EMPLOYEE PERFORMANCE WITH COMPETENCE AS A MEDIATING VARIABLE AT PT. ARMADA SAFARI SUCI - Ananda Danindra Al-Fasya; Fetty Poerwita Sarry (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The Hajj and Umrah travel industry in Indonesia is experiencing rapid growth, leading to increasingly fierce competition among travel agents in providing high-quality services to pilgrims. To maintain service quality and organizational performance, companies need to ensure that employees possess the necessary skills and competencies. HRD through training programs plays a crucial role in improving employee competency and performance, particularly in service-focused companies like PT. Armada Safari Suci. The purpose of this study is to analyze the effect of training on employee performance, with competency as a mediating variable. This study aims to investigate whether the company's training programs can improve employee competency and how this competency affects employee performance.This study used a quantitative approach with a descriptive research design. Data were collected through questionnaires distributed to PT. Armada Safari Suci employees. The data analysis method used statistical analysis to examine the relationship between training, competency, and employee performance.It is hoped that the results of this study will provide practical benefits for PT. Armada Safari Suci in improving employee training programs and enhancing employee performance. Academically, this research is expected to contribute to the development of human resource management literature, particularly in the areas of employee training and competency development.